Let's Explore Engineering - Levit, Joseph (Minneapolis Lerner Publications, 2019)
"An introduction to engineering and how it impacts people's lives."--
What is engineering? -- Engineering marvels.
Includes bibliographical references and index.
Keywords: Engineering -- Juvenile literature; Engineers -- Juvenile literature; Engineering; Engineers